OPTIMALISASI LUBUK LARANGAN SEBAGAI DAYA TARIK WISATA MELALUI PROMOSI MEDIA SOSIAL DESA TAMBANGAN JAE - Enni Sari Siregar; Nurintan Siregar; Nurliana Hutagalung; Ainun Nisa Btr (LPPM Universitas Al Muslim, 2024)
Lubuk Larangan is currently used as one of the tourist destinations that has great potential and many visitors consider it as a tourist spot as well as a fish farming location. By promoting tourism through various methods and media, the potential of this tourist destination can be developed more widely, in order to build the image and appeal of the tourist attraction. The use of social media as a means of tourism promotion is very effective in reaching more tourists. This community service activity aimed to introduce Lubuk Larangan through socialization to the community, especially members of the Karang Taruna of Tambangan Jae Village and was carried out in Lubuk Larangan. The method of implementing this community service activity is through socialization and direct discussion with Karang Taruna. The results of this activity showed that members of the Karang Taruna of Tambangan Jae Village gain an understanding of the importance of using social media as a means of promotion to introduce tourist attractions to make it better known and attract more visitors. Furthermore, participants are taught to create interesting content, such as photos and videos, which can be shared through various social media used.